2019 IEEE/ACM 41st International Conference on Software Engineering: Software Engineering in Practice (ICSE-SEIP) 2019
DOI: 10.1109/icse-seip.2019.00030
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Best Practices for Model-Based Systems Engineering Adoption in Embedded Systems Industry

Abstract: Model-based Systems Engineering (MBSE) advocates the integrated use of models throughout all development phases of a system development life-cycle. It is also often suggested as a solution to cope with the challenges of engineering complex systems. However, MBSE adoption is no trivial task and companies, especially large ones, struggle to achieve it in a timely and effective way. [Goal] We aim to discover what are the best practices and strategies to implement MBSE in companies that develop embedded software s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…Differing Opinions on Reported Best Practices. Furthermore, the validation survey conducted by Amorim et al (2019) shows that even on their final reported list of best practices, there are many differing opinions. In their study, 18 best practices were gathered from interviews, and the results were distributed to a set of engineers experienced in MBSE implementation.…”
Section: Company Location Affects Best Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Differing Opinions on Reported Best Practices. Furthermore, the validation survey conducted by Amorim et al (2019) shows that even on their final reported list of best practices, there are many differing opinions. In their study, 18 best practices were gathered from interviews, and the results were distributed to a set of engineers experienced in MBSE implementation.…”
Section: Company Location Affects Best Practicesmentioning
confidence: 99%
“…Out of the provided best practices, the only one that was agreed upon universally by all the engineers was "Technically prepared staff should support engineers" (Amorim et al 2019). The three most disagreed upon statements are outlined below with the percentage of respondents who disagreed with each statement.…”
Section: Company Location Affects Best Practicesmentioning
confidence: 99%
“…Most empirical studies on modeling in practice are case studies analyzing limited sets of models in specific contexts (e.g., [11,26,32,43,64]) or qualitative studies including interviews and surveys (e.g., [1,44,49]). Some studies approach the use of models in FOSS from a quantitative perspective, studying a large number and variety of projects.…”
Section: Relevance Of Open Source Models For Empirical Researchmentioning
confidence: 99%
“…To give a short overview of the state of research on the introduction of the MBSE approach in the industrial environment, some current publications are listed below. Amorim et al have summarized implementation strategies of MBSE for companies based on 10 interviews (Amorim et al 2019). Cameron and Adsit also developed conclusions about the introduction of MBSE in industrial companies from a large dataset (Cameron & Adsit 2018).…”
Section: Model-based Systems Engineeringmentioning
confidence: 99%
“…have summarized implementation strategies of MBSE for companies based on 10 interviews (Amorim et al. 2019). Cameron and Adsit also developed conclusions about the introduction of MBSE in industrial companies from a large dataset (Cameron & Adsit 2018).…”
Section: State Of the Artmentioning
confidence: 99%